The Impact of Corporate Social Responsibility Disclosure on Corporate Reputation: A Non-professional Stakeholder Perspective - Axjonow, Anastasia (Journal of business ethics, 2018)
This paper examines the impact of corporate social responsibility (CSR) disclosure on corporate reputation as perceived by non-professional stakeholders. Proponents of CSR disclosure argue that CSR disclosure can be considered as a tool for reputation management. We empirically investigate this claim using a reputation index which tracks the general public’s perceptions of corporate reputation over time. In our analysis, we focus on disclosure in stand-alone CSR reports and control for CSR performance. We find that, in contrast to the common belief, stand-alone CSR reports do not influence corporate reputation among non-professional stakeholders. However, we are able to document that stand-alone CSR reports influence corporate reputation among professional stakeholders. We also provide some evidence that transparent CSR disclosure on corporate websites can influence corporate reputation among non-professional stakeholders.